Descending Perineum Associated With Pelvic Organ Prolapse Treated by Sacral Colpoperineopexy and Retrorectal Mesh Fixation: Preliminary Results - Nessi, Aude; Kane, Aminata; Vincens, Etienne; Salet-Lizée, Delphine; Lepigeon, Karine; Villet, Richard (Frontiers in Surgery, 2018)
Introduction and hypothesis Descending Perineum Syndrome (DPS) is a coloproctologic disease and the best treatment for it is yet to be defined. DPS is frequently associated with pelvic organ prolapse (POP) and it is reasonable to postulate, that treatment of POP will also have an impact on DPS. We aimed to evaluate the subjective satisfaction and improvement of DPS for patients who have undergone a sacral colpoperineopexy associated with retrorectal mesh for concomitant POP. Methods: This retrospective cohort study, conducted between February 2010 and May 2016 included all women who have undergone surgery to treat POP and DPS. Improvement of POP was assessed clinically and subjective satisfaction was assessed with a questionnaire. Results: Among the 37 operated patients, 31 responded to the questionnaire and 77,4% were satisfied with this surgical procedure. 94,6% were objectively cured for POP. There was a 60% improvement rate for constipation, 63,5% and 68% were cured or improved for ODS and the need for digital maneuvers respectively. Conclusion: Sacralcolpoperineopexy associated with retro rectal dorsal mesh appears to objectively and subjectively improves pelvic organ prolapse associated with DPS.